Obtención de Agua Mediante Condensación de la Humedad del Aire de la Ciudad de Santa Marta - Mosquera Zuñiga, Yissier; Ramirez Lizca, Marlon Alberto (Universidad Antonio Nariño, 2021)
This research assumed as its main objective to create a small-scale mechanism that produced water from the humidity of the air, with this prototype it was sought to mitigate the scarcity of the liquid in some sectors of the city of Santa Marta since the water supply It is not constant and thus contribute to the problem of this population. This process of water collection becomes the basis of the cooling cycle, where its main function is to cool an air stream in the evaporator until it reaches the point temperature. from dew to condensation of air humidity. The results obtained during the research resulted in the collection of 1,186 liters of water at an average ambient temperature of 27 to 30ºC at an average relative humidity of 70 to 87% for 15 hours, data that was taken during the tests and with the help of a digital hygrometer with an external sensor.